Adolescent access to and utilization of health services in the Gbêkê and Hambôl regions of Côte d'Ivoire: A qualitative study exploring the perceptions of adolescents, caregivers, and health care workers - Donahue, Chantal (My University, 2018)
Adolescence is a critical time for physical, cognitive, social and emotional development, yet adolescents are prone to unique barriers and unmet needs for receiving proper health care services and information. This study explored barriers and facilitators to adolescent (15-19 years) access to and utilization of health services in two regions of Côte d’Ivoire. Focus group discussions were conducted with adolescent females and males, caregivers, and health care workers at eight health facilities. Barriers and facilitators emerged within three themes: cultural, structural, and “accueil,” a French word that translates to “welcome” but also encompasses overall feelings and experiences of a situation. Cultural barriers included community beliefs and stigma, and adolescent knowledge, while caregiver support and medical preference were both barriers and facilitators. Structural barriers included financial costs, distance to health facilities, waiting times, and lack of supplies and medications. Feelings of fear, shame and discomfort were barriers related to “accueil” while interactions with health care workers were both barriers and facilitators. Similarities and differences in perspectives between adolescents, caregivers, and health care workers were present. Future work to increase adolescent access to and utilization of health services should take into consideration both recommendations from adolescents and the interconnectedness of the barriers they face to create multidimensional approaches that improve health outcomes for this priority population.
Thesis (Master's)--University of Washington, 2018
Keywords: adolescent friendly health services; adolescent health; Côte d’Ivoire; Public health; Global Health